Phytoplasma infection in tomato is associated with re-organization of plasma membrane, ER stacks, and actin filaments in sieve elements - Buxa, Stefanie V.; Degola, Francesca; Polizzotto, Rachele; De Marco, Federica; Loschi, Alberto; Kogel, Karl-Heinz; di Toppi, Luigi Sanità; van Bel, Aart J. E.; Musetti, Rita (Frontiers in Plant Science, 2015)
Phytoplasmas, biotrophic wall-less prokaryotes, only reside in sieve elements of their host plants. The essentials of the intimate interaction between phytoplasmas and their hosts are poorly understood, which calls for research on potential ultrastructural modifications. We investigated modifications of the sieve-element ultrastructure induced in tomato plants by ‘Candidatus Phytoplasma solani’, the pathogen associated with the stolbur disease. Phytoplasma infection induces a drastic re-organization of sieve-element substructures including changes in plasma membrane surface and distortion of the sieve-element reticulum. Observations of healthy and stolbur-diseased plants provided evidence for the emergence of structural links between sieve-element plasma membrane and phytoplasmas. One-sided actin aggregates on the phytoplasma surface also inferred a connection between phytoplasma and sieve-element cytoskeleton. Actin filaments displaced from the sieve-element mictoplasm to the surface of the phytoplasmas in infected sieve elements. Expression analysis revealed a decrease of actin and an increase of ER-resident chaperone luminal binding protein (BiP) in midribs of phytoplasma-infected plants. Collectively, the studies provided novel insights into ultrastructural responses of host sieve elements to phloem-restricted prokaryotes.